DERIVATIONAL AFFIXES IN STUDENTS’ SHORT STORIES AT STATE SENIOR HIGH SCHOOL (SMAN) 1 KARANGANYAR - Pepsi Febriyanti; Budi Santosa, Rochmat; Rohardiyanto, Irwan (Mahakarya: Jurnal Mahasiswa Ilmu Budaya, 2024)
This research aims to analyze the realization of derivational affixes in eleventh-grade students’ writing assignments in the specialization class, which is literature class at State Senior High School (SMAN) 1 Karanganyar. Plag, Carstairs and McCarthy, and Haspelmath and Sims were the theories used in this research. These theories are related to the characteristics of derivational affixes, the kinds of word class changes in derivational affixes, and the categories of derivational affixes. This research used a descriptive qualitative method with the document analysis technique to gather data from eleventh-grade students’ writings.  The researcher found 285 words formed through the derivational affixes process. While derivational infixes were not found in the study, the findings show that derivational suffixes are more widely used than derivational prefixes. In short, students applied derivational affixes grammatically correctly in their writings.